The Relationship Of Learning Outcomes To The Desired Of Vocational School Students To Enter College - Rahmi, Ulfa; Yelfi, Reno (Universitas Negeri Padang, 2023)
This study aims to determine the desire of students to enter tertiary institutions with student learning outcomes and to analyze whether there is a relationship between student learning outcomes and students' desires to enter tertiary institutions. This research method is quantitative with a correlational approach. The results showed that the category of respondent's achievement level (TCR) for students' desire to enter higher education was 3.97 in the high category. There is no significant relationship between student learning outcomes and students' desire to enter college.